Restoring Function After Severe Spinal Cord Injury Through BioLuminescent-OptoGenetics - Petersen, Eric D.; Sharkey, Erik D.; Pal, Akash; Shafau, Lateef O.; Zenchak-Petersen, Jessica; Peña, Alex J.; Aggarwal, Anu; Prakash, Mansi; Hochgeschwender, Ute (Frontiers in Neurology, 2022)
The ability to manipulate specific neuronal populations of the spinal cord following spinal cord injury (SCI) could prove highly beneficial for rehabilitation in patients through maintaining and strengthening still existing neuronal connections and/or facilitating the formation of new connections. A non-invasive and highly specific approach to neuronal stimulation is bioluminescent-optogenetics (BL-OG), where genetically expressed light emitting luciferases are tethered to light sensitive channelrhodopsins (luminopsins, LMO); neurons are activated by the addition of the luciferase substrate coelenterazine (CTZ). This approach utilizes ion channels for current conduction while activating the channels through the application of a small chemical compound, thus allowing non-invasive stimulation and recruitment of all targeted neurons. Rats were transduced in the lumbar spinal cord with AAV2/9 to express the excitatory LMO3 under control of a pan-neuronal or motor neuron-specific promoter. A day after contusion injury of the thoracic spine, rats received either CTZ or vehicle every other day for 2 weeks. Activation of either neuron population below the level of injury significantly improved locomotor recovery lasting beyond the treatment window. Utilizing histological and gene expression methods we identified neuronal plasticity as a likely mechanism underlying the functional recovery. These findings provide a foundation for a rational approach to spinal cord injury rehabilitation, thereby advancing approaches for functional recovery after SCI. Summary Bioluminescent optogenetic activation of spinal neurons results in accelerated and enhanced locomotor recovery after spinal cord injury in rats.